The Effectiveness of Peer Counseling in Solving Problems Adapting as a Manager of Dormitory in the Pesantren - Jaziela Huwaida; Hanif Amrullah (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
Modern Islamic Institution Darussalam Gontor has begun to mandate itsselected class four students as dormitory managers in adolescents who are vulnerablein adapting of new things. Based on this problem, the researcher wants to examinethe effectiveness of peer counseling on class four dormitory managers in overcomingthe problem of adapting as manager Dormitory. This study aims to 1) analyze theproblems they face in adapting as manager Dormitory 2) explain the effectiveness ofpeer counseling in overcoming the problem of adapting to the new mandate inPesantren environment. To achieve its objectives, researcher used qualitativemethods through interviews with several managers and related parties as well asdocumenting relevant sources. The results of this study are 1) The problems faced aredivided into 2 namely self-adaptation as managers and social adaptation to theirresponsibilities. Internal problems cause such as: embarrassed, awkward, inferior,and nervous. 2) Regarding the effectiveness of peer counseling in overcoming thisproblem, it can be supported by various programs such as regular meetings betweenadministrators, joint breaks per dorm zone, and daily friendship between them. It canbe concluded that peer counseling is one of the effective methods in dealing withadolescent problems, especially as new administrators of the hostel. This research isexpected to understand properly the adaptation of dorm managers’ challenges incarrying out their duties and help overcome existing problems.